ENDOPHY BACTERIAL ISOLATE TEST FOR INHIBITORS OF LEAF DROPPING DISEASE (Pestalotiopsis sp) IN THE LABORATORY - Fenty Maimunah Simbolon; Syamsafitri; Mindalisma; Ramayanti A (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
This research was conducted at the Sungai Putih Research Center, Rubber Research Center, Kec. Galang, Kab. Deli Serdang North Sumatra, North Sumatra Province. This research was conducted from December 2020 to April 2021. The aim of this study was to test the ability of Endofid bacterial isolates to inhibit the development of leaf fall disease (Pestalotiopsis sp) in the laboratory. The study used a non-factorial completely randomized design (RAl) with endophytic bacteria treatment with 6 levels of treatment, namely control (SPE0), isolate 1 from Sungai Putih (SPE1), isolate 2 from Sungai Putih (SPE2), isolate 3 from Bandar Betsi (BBE3). ), isolate 4 from Bandar Betsi (BBE4), isolate 5 from Bandar Betsi (BBE5). The parameters observed were the identification of the fungus Pestalotiopsis sp and indophytic bacteria, the percentage of broad inhibition of the fungus Pestalotiopsis sp, the Antagonist Test of Endophytic Bacteria against Pestalotiopsis sp by In Vitro, the Pathogenicity Test of Chili Against Selected Endophytic Bacteria, the Growth Test of Chili Plants against Selected Endophytic Bacteria. The results of statistical analysis showed that the endophytic bacterial isolate had a significant effect on the percentage of inhibition of the area of Pestalotiopsis sp. The growth of chili seed sprouts by immersing the endophytic bacteria solution resulted in a smaller percentage than the control, but it could increase the growth of plant height and root length of chili plants.